Human Settlement and Environmental Exploitation of Valcamonica-Valtrompia Watershed from the Beginning of the Holocene to the Middle Ages - BIAGI, Paolo; STARNINI, Elisabetta (2015)
Abstract - This paper discusses some aspects of the highaltitude peopling of Valcamonica-Valtrompia watershed within the general pattern of the prehistoric and historic exploitation of the Central Alpine arc of northern Italy. Research carried out during the last 30 years has shown extensive evidence of humanoccupation starting from the end of the Late Palaeolithic. Moreinformation is available for the beginning of the Holocene, witnessing the ascent of the watershed by groups of Mesolithic hunter-gatherers as soon as the alpine pastures had been freed from the ice sheet. The highland zone was exploited againduring the Bronze Age, as shown by the recovery of flintarrowheads from present-day footpaths, and a good set of radiocarbon dates. More recent, though sporadic occupations are documented during the Iron Age and the early Medieval period.